Development and Simulation of Sulfur‐doped Graphene Supported Platinum with Exemplary Stability and Activity Towards Oxygen Reduction. (1st April 2014) - Higgins, Drew; Hoque, Md Ariful; Seo, Min Ho; Wang, Rongyue; Hassan, Fathy; Choi, Ja‐Yeon; Pritzker, Mark; Yu, Aiping; Zhang, Jiujun; Chen, Zhongwei
<x xml:space="preserve">Abstract</x> Sulfur‐doped graphene (SG) is prepared by a thermal shock/quench anneal process and investigated as a unique Pt nanoparticle support (Pt/SG) for the oxygen reduction reaction (ORR). Particularly, SG is found to induce highly favorable catalyst‐support interactions, resulting in excellent half‐cell based ORR activity of 139 mA mgPt−1 at 0.9 V vs RHE, significant improvements over commercial Pt/C (121 mA mgPt−1) and Pt‐graphene (Pt/G, 101 mA mgPt−1). Pt/SG also demonstrates unprecedented stability, maintaining 87% of its electrochemically active surface area following accelerated degradation testing. Furthermore, a majority of ORR activity is maintained, providing 108 mA mgPt−1, a remarkable 171% improvement over Pt/C (39.8 mA mgPt−1) and an 89% improvement over Pt/G (57.0 mA mgPt−1). Computational simulations highlight that the interactions between Pt and graphene are enhanced significantly by sulfur doping, leading to a tethering effect that can explain the outstanding electrochemical stability. Furthermore, sulfur dopants result in a downshift of the platinum d‐band center, explaining the excellent ORR activity and rendering SG as a new and highly promising class of catalyst supports for electrochemical energy technologies such as fuel cells.